Importins and Exportins Regulating Allergic Immune Responses - Ankita Aggarwal; Devendra K. Agrawal (Mediators of Inflammation, 2014)
Nucleocytoplasmic shuttling of macromolecules is a well-controlled process involving importins and exportins. These karyopherins recognize and bind to receptor-mediated intracellular signals through specific signal sequences that are present on cargo proteins and transport into and out of the nucleus through nuclear pore complexes. Nuclear localization signals (NLS) present on cargo molecules to be imported while nuclear export signals (NES) on the molecules to be exported are recognized by importins and exportins, respectively. The classical NLS are found on many transcription factors and molecules that are involved in the pathogenesis of allergic diseases. In addition, several immune modulators, including corticosteroids and vitamin D, elicit their cellular responses by regulating the expression and activity of importin molecules. In this review article, we provide a comprehensive list of importin and exportin molecules and their specific cargo that shuttled between cytoplasm and the nucleus. We also critically review the role and regulation of specific importin and exportin involved in the transport of activated transcription factors in allergic diseases, the underlying molecular mechanisms, and the potential target sites for developing better therapeutic approaches.